(untitled) (Desarrollo, Estado y Espacio, 2025)
Based on a literature review, this paper aims to contribute to the reflections and discussions on qualitative approaches to the conceptualisation of state spatiality. Inspired by anthropological studies on the state, which have multiplied since the 1970s in the discipline, it seeks to account for the main debates on the scalar question and the state problem. These topics represent the two blocks of reflection in the text. The dialogue with anthropology in order to think about the state and the scalar derives from the power of this science to denaturalise social processes, specifically political problems. In this way, methodology and theory are knotted together in the text for reflection, paying special attention to ethnography as a methodological strategy. The results derive, then, from a literature review where perspectives on the state (Abrams, 2015; Mitchell, 2015; Gupta, 2015), problems of governance (Rose and Miller, 1992) and the scalar question produced in the neoliberal context (Brenner et. al., 2011) are brought into dialogue. We propose a methodological theoretical contribution that we consider useful for those who study situated processes that are traversed by the global dynamics of capital.